2014
DOI: 10.1016/j.snb.2013.11.046
|View full text |Cite
|
Sign up to set email alerts
|

Reflection based extraordinary optical transmission fiber optic probe for refractive index sensing

Abstract: Fiber optic probes for chemical sensing based on the extraordinary optical transmission (EOT) phenomenon are designed and fabricated by perforating subwavelength hole arrays on the gold film coated optical fiber endface. The device exhibits a red shift in response to the surrounding refractive index increases with high sensitivity, enabling a reflection-based refractive index sensor with a compact and simple configuration. By choosing the period of hole arrays, the sensor can be designed to operate in the near… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 21 publications
(19 reference statements)
0
13
0
Order By: Relevance
“…RI sensors have been patterned either on the sidewall of optical fiber [18], fiber tip [19][20][21][22][23][24][25][26][27] or both [28 29] for transmission/reflection measurements. For sensors on the tip of the optical fiber, reflection-based measurements only require one port into the sensing media, and the interrogation area has been shown to approach the area of the fiber core (as small as 1/2500 mm 2 for single mode fiber) [21]. Focused Ion Beam (FIB) and Electron Beam Lithography (EBL) are the most common methods to pattern RI sensors on the facet of optical fiber [30].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…RI sensors have been patterned either on the sidewall of optical fiber [18], fiber tip [19][20][21][22][23][24][25][26][27] or both [28 29] for transmission/reflection measurements. For sensors on the tip of the optical fiber, reflection-based measurements only require one port into the sensing media, and the interrogation area has been shown to approach the area of the fiber core (as small as 1/2500 mm 2 for single mode fiber) [21]. Focused Ion Beam (FIB) and Electron Beam Lithography (EBL) are the most common methods to pattern RI sensors on the facet of optical fiber [30].…”
Section: Introductionmentioning
confidence: 99%
“…Focused Ion Beam (FIB) and Electron Beam Lithography (EBL) are the most common methods to pattern RI sensors on the facet of optical fiber [30]. For example, Lan et al [21] demonstrated FIB milling an square lattice of subwavelength holes on the tip of optical fiber to achieve a sensitivity of 573 nm/RIU and Lin et al [23] patterned nanodots using EBL to produce sensors with 196 nm/RIU. The cost of patterning is a significant obstacle to the practical use of optical fiber-based LSPR sensors.…”
Section: Introductionmentioning
confidence: 99%
“…The exploitation of surface plasmon resonances and localized surface plasmon resonances (LSPRs) within subwavelength apertures and nanoparticles/structures for the detection of changes in refractive index (RI) (typically seen as wavelength shifts of several hundred nanometers per refractive index unit (RIU)) has been previously reported in the literature . However, the majority of these studies have used devices fabricated from gold with resonances located in the red and infrared regions of the electromagnetic spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…Over the years, many approaches have been explored including (but not limited to) interferometers, [3][4][5] fiber gratings, 6,7 long period fiber gratings, [8][9][10] surface plasmonic resonance devices, 11 multimode interference devices, 12 attenuated total internal reflectance sensors, 13,14 extraordinary optical transmission devices, 15 photonic crystal fibers, 16 and whispering gallery mode (WGM) optical microresonators 17 and microlasers. 18 These fiber optic devices have a small size and can be used to measure the RI of a sample with a small volume.…”
Section: Introductionmentioning
confidence: 99%